Adoption of internet banking among bank customers in Kota Bharu / Nur Adilah Roslan - Roslan, Nur Adilah (2011)
According to Bank Negara Malaysia (BNM) websites, Internet banking provides a fast and convenient way of performing common banking transactions, such transferring funds from savings account to current account, or even to a third party's account. Through Internet banking, payments to relevant parties also can be made, such as utility bills and assessment tax. Under the Bank Negara Malaysia guidelines, all licensed banking institutions in Malaysia are allowed to establish the informational Web sites. Only banking institutions under the banking and Financial Institutions Act 1989 and the Islamic Banking Act 1983 are allowed to offer Internet banking services in Malaysia (Bank info, 2005). The main primary of this study is to determine the adoption of internet banking among bank customers in Kota Bharu. In this research, the researcher had used convenience sampling from non-probability sampling to distribute 180 questionnaires among bank customers in Kota Bharu. The data were analyzed by using SPSS through the descriptive analysis, regression analysis and reliability analysis .An analysis of the data also were made by using The Structural Equation Modeling (SEM) using AMOS: This statistical technique is employed to model the inter-relationship among the variables in the study (adoption of internet banking, perceived usefulness, ease of use trust, compatibility and costs saved) simultaneously. This study indirectly helped to promote internet banking service to the residents in Kota Bharu and also to get the reason why customers not using this services. This research also will help financial institutions especially the bank to improve internet banking services thus to fit with the customer’s needs and wants. From the analysis, the researcher found that perceived usefulness, ease of use and compatibility has a significant relationship with the adoption of internet banking. However, trust and costs saved has a significant negative relationship between adoption of internet banking